Experimental study of the stability of a fiber embedded in a soft gel under torsional and axial loading - Nur Ashirah Binte Mohamad Sahar (Nanyang Technological University, 2023)
This document discusses the use of polymer fibers in biomedical engineering and their mechanical properties. The extracellular matrix (ECM) plays a critical role in cell growth, movement, and other functions, and polymer fibers are frequently used because they closely resemble the ECM. The document also explores the mechanical behaviour of fiber-reinforced solids under compression and torsion, and the importance of understanding how the structure corresponds mechanically, especially in the biomedical field. The paper aims to investigate the stability of a fiber embedded in a soft gel under combined torsional and axial loads and analysis of the results using simple mechanics provides insights into how these combined loads are important in the biomedical field. The findings of this study could have important implications for the design of fiber- reinforced composite materials and soft biomaterials. Understanding how fibers behave under combined loads of compression and torsion could help improve the performance of these materials in various biomedical applications. Additionally, the use of a simple experimental setup using hemp fibers and food gel as a soft embedding medium could provide a cost-effective and accessible method for investigating the behaviour of fibers in soft composites. Further research in this area could lead to the development of new materials with improved mechanical properties and greater potential for use in biomedical engineering.